Investigation of DMSO-Induced Conformational Transitions in Human Serum Albumin Using Two-Dimensional Raman Optical Activity Spectroscopy - Batista, Andrea N. L. [UNESP]; Batista, Joao M. [UNESP]; Ashton, Lorna; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Blanch, Ewan W. (Wiley-Blackwell, 2014)
Recent Raman and Raman optical activity (ROA) results have demonstrated that dimethyl sulfoxide (DMSO) induces the selective conversion of alpha-helix motifs into the poly(L-proline) II (PPII) helix conformation in an array of proteins, while beta-sheets remain mostly unaffected. Human serum albumin (HSA), a highly alpha-helical protein, underwent the most dramatic changes and, therefore, was selected as a model for further investigations into the mechanism of this conformational change. Herein we report the use of two-dimensional ROA correlation analysis applying synchronous, autocorrelation, and moving windows approaches in order to understand the conformational transitions in HSA as a function of DMSO concentration. Our results indicate that the destabilization of native alpha-helix starts at DMSO concentrations as little as 20% in water (v/v), with the transition to PPII helix being complete at similar to 80% DMSO. These results clearly indicate that any protein preparation containing relatively low concentrations of DMSO should consider possible disruptions in alpha-helical domains. (C) 2014 Wiley Periodicals, Inc.
Keywords: ROA; 2DCOS; HSA; moving windows; protein; secondary structure; PPII helix